2006
DOI: 10.2337/dc06-0974
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Feeding and Risk for Childhood Obesity

Abstract: OBJECTIVE -We sought to evaluate whether maternal diabetes or weight status attenuates a previously reported beneficial effect of breast-feeding on childhood obesity.RESEARCH DESIGN AND METHODS -Growing Up Today Study (GUTS) participants were offspring of women who participated in the Nurses' Health Study II. In the present study, 15,253 girls and boys (aged 9 -14 years in 1996) were included. Maternal diabetes and weight status and infant feeding were obtained by maternal self-report. We defined maternal over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(123 citation statements)
references
References 39 publications
7
111
2
3
Order By: Relevance
“…This association was similar to that among offspring of normal-weight women (n ϭ 8,617) and overweight women (n ϭ 6,190) without diabetes during pregnancy (48). Another study of 324 offspring of mothers with GDM from Berlin, Germany, found that exclusive breastfeeding for Ͼ3 months was associated with a lower risk of overweight (Ͼ90th percentile) at ages 2-8 years (OR 0.55, 95% CI 0.33-0.91), but lower risk of overweight was limited to offspring of obese GDM mothers (49).…”
Section: Breastfeeding and Subsequent Overweight And Diabetes In Offssupporting
confidence: 77%
“…This association was similar to that among offspring of normal-weight women (n ϭ 8,617) and overweight women (n ϭ 6,190) without diabetes during pregnancy (48). Another study of 324 offspring of mothers with GDM from Berlin, Germany, found that exclusive breastfeeding for Ͼ3 months was associated with a lower risk of overweight (Ͼ90th percentile) at ages 2-8 years (OR 0.55, 95% CI 0.33-0.91), but lower risk of overweight was limited to offspring of obese GDM mothers (49).…”
Section: Breastfeeding and Subsequent Overweight And Diabetes In Offssupporting
confidence: 77%
“…After these recent meta-analyses and systematic reviews, at least 13 additional observational studies were published. Six of them suggested a decreased risk for obesity with breastfeeding, [58][59][60][61][62][63] while five 42,64-67 did not detect any association. One of the largest studies to date showed a protective effect of breastfeeding only in some subgroup analyses.…”
Section: No Data Experimental Reproducibility In Humansmentioning
confidence: 90%
“…Breastfeeding may play a role in preventing the development of allergies and appears to protect children from obesity and atherosclerosis. [14][15][16] The relationship between lactation and obesity is not fully understood, probably because of the different methods that women use to balance their energy intake and expenditure.…”
Section: Introductionmentioning
confidence: 99%